Design Of Retaining Wall In Landslide Areas (Case Study: Nagrak Street, Bandung Regency, West Java) - Setiawan, Asep; Agustian, Yanyan; Radhitya Akbar, Sandy (International Journal of Psychosocial Rehabilitation, 2020)
The rapid development of traffic volume and the presence of natural phenomena can affect the deterioration of the road structure and its complementary buildings. One of the natural phenomena that arise on Jalan Nagrak is landslides, so we need the best and economical treatment by paying attention to the safety and comfort of road users. The purpose of this research is to deal with landslides on Jalan Nagrak by planning the construction of a Soil Retaining Wall in areas with unstable soil conditions and certain slopes. This study refers to data at the location conducted in accordance with American Standard Testing and Material (ASTM) procedures. From the results of the study it was found that the condition of Nagrak road damage in the form of cracks and subsidence in the pavement layer leading to slope collapse, selected Avalanche Handling Technology in the form of Reconstruction of the retaining wall using a masonry retaining wall with a bore pile foundation. The foundation of the retaining wall is placed under the skid plane at least 2 m and the width of the foundation 1.1 m.